ADMINISTRATIVE AND LEGAL REGULATION IN THE FIELD OF THE CIVIL AVIATION OF UKRAINE - Москаленко, Сергій Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
The purpose of the article: the purpose of the article is to determine the peculiarities of the administrative and legal regulation in the field of civil aviation of Ukraine and, on the basis of the analysis of legal literature and normative legal acts, to propose an author’s definition of the said concept. Methods of research: using the dialectical method of cognition allowed to concentrate accumulated scientific knowledge and practice of applying legislation on the implementation of state control and administrative-legal support in the field of civil aviation. Results: based on the analysis of legal literature, national, aviation legislation, the author’s definition of administrative-legal regulation in the field of civil aviation was proposed. Discussion: problems of state control and administrative regulation in the field of civil aviation.